Bilateral Trade Flows, The Gravity Equation, and Functional Form - Sanso, Marcos; Cuairan, Rogelio; Sanz, Fernando (The Review of Economics and Statistics, 1993)
The gravity equation has been frequently and successfully used for nearly thirty years to further understanding of the determinants of bilateral trade flows across countries and, subsequently, to analyze commercial policy measures. A maintained hypothesis by the applied literature on international trade as gravity equation loglinearity is questioned in this paper since the possibility of a general functional form is open through Box-Cox transformations. Using data corresponding to the sixteen OECD most developed countries from 1964 to 1987 the authors reach the conclusion that the optimal functional form is slightly, yet statistically, different from the loglinear form in every year of the sample and they are able to propose one unique functional form suitable for all the sample period. Copyright 1993 by MIT Press.